2009
DOI: 10.1007/s10750-009-9923-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of invasive benthic macroinvertebrates on assessment methods of the EU Water Frame Work Directive

Abstract: The assessment of the ecological status of aquatic ecosystems for the implementation of the European Water Framework Directive is based on different methods, many of which include the study of macroinvertebrate organisms. We examined whether and how invasive species affect the calculation of metrics used for fresh water assessment utilizing data from different substrate types in the streams of Central Germany. In these streams, the proportion of macroinvertebrate invasives increased from a very low fraction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…For instance, our mesocosm study shows that D. villosus is far more predatory towards other taxa than the resident amphipod species it may be replacing, such as G. pulex (MacNeil & Platvoet, 2005) or G. duebeni (Dick & Platvoet, 2000), supporting the conjecture that increased predation results in the decline of residents. From German river field surveys, Arndt et al (2009) found that D. villosus presence could undermine the usefulness of the GSI, and now our study shows that D. villosus has the potential to undermine the reliability of an additive biotic index such as the BMWP score. For instance, the aggressive and predatory activities of D. villosus could cause a decline in resident predators such as Ecnomidae (Trichoptera), as they are outcompeted for shared prey species.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…For instance, our mesocosm study shows that D. villosus is far more predatory towards other taxa than the resident amphipod species it may be replacing, such as G. pulex (MacNeil & Platvoet, 2005) or G. duebeni (Dick & Platvoet, 2000), supporting the conjecture that increased predation results in the decline of residents. From German river field surveys, Arndt et al (2009) found that D. villosus presence could undermine the usefulness of the GSI, and now our study shows that D. villosus has the potential to undermine the reliability of an additive biotic index such as the BMWP score. For instance, the aggressive and predatory activities of D. villosus could cause a decline in resident predators such as Ecnomidae (Trichoptera), as they are outcompeted for shared prey species.…”
Section: Discussionmentioning
confidence: 51%
“…The accuracy of other indices commonly used in Central Europe, such as the Belgian Biotic Index (BBI - Gabriels, Goethals & De Pauw, 2005) and the German Saprobic Index (GSI - Arndt et al, 2009), has also been shown to be compromised by the presence of abundant invaders, such as the Asian clams Corbicula spp. There remains a lack of consensus on inclusion ⁄ exclusion or assigned score ⁄ tolerance values with respect to invaders and biotic indices (Gabriels et al, 2005;Arndt et al, 2009). There remains a lack of consensus on inclusion ⁄ exclusion or assigned score ⁄ tolerance values with respect to invaders and biotic indices (Gabriels et al, 2005;Arndt et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Various metrics of ecological status, such as the BMWP score, the ASPT, species richness, EPT taxa number, Shannon-Wiener diversity or German saprobic index, have been shown to be affected by the presence of invasive species or at least related to it (Arbačiauskas et al, , 2011Gumuliauskaitė and Arbačiauskas, 2008;Arndt et al, 2009;MacNeil et al, 2010). Our lake macroinvertebrate data did not reveal any significant impact of biocontamination on the LLMI or its core metrics.…”
Section: Links Between the Metrics Of Biocontamination And Ecologicalmentioning
confidence: 47%
“…Interestingly, duck do not feed on C. fluminea, which has thicker valves than D. polymorpha and lives buried in the upper layer of sand . Several studies suggest that alien species generally have a negative impact on native communities (Strayer, 1999(Strayer, , 2010Rahel, 2002;Arndt et al, 2009). However, Botts et al (1996) demonstrated in a field experiment that Dreissena species can change the physical structure of sandy habitats which in turn may lead to increased densities of native species.…”
Section: Discussionmentioning
confidence: 99%